2016
DOI: 10.1016/j.jana.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Displacement and HIV: Factors Influencing Antiretroviral Therapy Use by Ethnic Shan Migrants in Northern Thailand

Abstract: Migrant populations face increased HIV vulnerabilities, including limited access to antiretroviral therapy (ART). Civil conflict in Myanmar has displaced thousands of people from the minority Shan ethnic group into northern Thailand, where they bear a disproportionate HIV burden. To identify barriers and facilitators of ART use in this population, we conducted a rapid ethnographic assessment and case study with a clinical sample of Shan migrants receiving treatment for HIV in a district hospital in Chiang Mai,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Murray et al 42 used their rapid ethnography to inform local policies, and Agyepong and Manderson31 used the study findings to develop a field manual for the rapid assessment of the cultural aspects of malaria. Findings were shared mainly through reports and academic publications, but some of the authors also reported sharing the results of studies through meetings and workshops with relevant stakeholders 35 38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murray et al 42 used their rapid ethnography to inform local policies, and Agyepong and Manderson31 used the study findings to develop a field manual for the rapid assessment of the cultural aspects of malaria. Findings were shared mainly through reports and academic publications, but some of the authors also reported sharing the results of studies through meetings and workshops with relevant stakeholders 35 38…”
Section: Resultsmentioning
confidence: 99%
“…Exceptions were the articles by Murray et al 42 and Harte et al ,44 which presented detailed descriptions of coding processes. In most articles, it was not clear if analysis was carried out using ‘traditional’ techniques or if rapid approaches were also used to analyse and interpret the data 2 49–51.…”
Section: Discussionmentioning
confidence: 99%
“…The geopolitical context of the host country creates barriers to the testing and treatment of sexually transmitted infections and HIV across the globe (1,62,64). Laws and policies have historically limited migration of HIV-positive individuals into various countries, not for purposes of health promotion but to prevent the spread of the virus.…”
Section: Political Climatementioning
confidence: 99%
“…In our quantitative study [ 21 ], which included 442 participants aged 15–24 years, more than half (57%) of participants were sexually active, but the majority had never used condom, and a significantly low proportion of young MWs reported using condoms consistently. The majority of our participants were from the Shan ethnic group, [ 21 ] a group primarily from Shan State in Myanmar and constitutes one of the largest groups of cross-border MWs in Chiang Mai province [ 1 , 22 , 23 ]. The Shan in Thailand include two major groups.…”
Section: Introductionmentioning
confidence: 99%
“…The second group includes both documented and undocumented Shan MWs who have migrated in search of economic opportunities in Thailand. Many Shan work in low-paid jobs including domestic work, construction, agricultural labor, and sex work [ 1 , 22 , 23 ]. Changes in social and traditional norms of the Shan living in Thailand have been reported anecdotally.…”
Section: Introductionmentioning
confidence: 99%